Selenoprotein N‐related myopathy: a retrospective natural history study to guide clinical trials. Issue 11 (10th October 2020) - Silwal, Arpana; Sarkozy, Anna; Scoto, Mariacristina; Ridout, Deborah; Schmidt, Anne; Laverty, Aidan; Henriques, Matilde; D'Argenzio, Luigi; Main, Marion; Mein, Rachael; Manzur, Adnan Y; Abel, Francois; et al.
Abstract: Objective: To describe clinical features and disease progression of Selenoprotein N‐related myopathy in a large multicenter cohort of patients. Methods: Cross‐sectional multicenter data analysis of 60 patients (53 families) with Selenoprotein N‐related myopathy and single‐center retrospective longitudinal analysis of 25 patients (21 families) over a median period of 5.3 years. Results: The majority of patients (46/60, 77%) presented before age 2 years with hypotonia, poor head/neck control, and developmental delay. At last assessment (median age 14 years; range 2.5 to 36 years), 10/60 patients had minimal or no ambulation. Ventilatory support was initiated in 50/60 patients at a mean Forced Vital Capacity (FVC) of 38% and at a median age of 13 years. Forty‐five/60 patients developed scoliosis (at median age 12.1 years) and 18 had scoliosis surgery at a median age of 13.6 years. Five children needed nasogastric feeds and/or gastrostomy. Longitudinal data analysis on 25 patients showed progressive decline of Hammersmith functional motor scores (estimated annual change −0.55 point), time to walk 10 meter, time standing from sitting, and from lying. Sixteen patients had weights < 2nd centile. The estimated change in FVC % per year was −2.04, with a 95% CI (−2.94, −1.14). Conclusions: This comprehensive analysis of patients with Selenoprotein N‐related myopathy further describes the clinical course of this rare condition. The observed functional motor and respiratory data provide evidence of the slow decline patients experience over time which is useful when considering therapeutic intervention.